ЗАКОНОДАТЕЛЬНАЯ БАЗА РЫНОЧНЫХ РЕФОРМ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Ктайбеков, А.М. (SCIENCE and SOCIETY, 2024)
The article examines the evolution of legislation in the Republic of Karakalpakstan since Uzbekistan’s independence. In the context of the transition from a centralized economic model to a market model, the article highlights the role of the legislative framework in stimulating entrepreneurial activity, protecting property rights and regulating the market.